Experiment Tool Development of Circular Motion Experiment with Belt-Connected Wheels Using Hall Effect Sensor Based on IoT - Yuhelmi Farah Difa; Yulkifli; Asrizal; Yenni Darvina (Research on Instrumentation, 2024)
Innovation in educational tools is crucial for improving the learning experience in physics experiments. This study presents the design and development of an IoT-based experimental tool for analyzing wheel dynamics. The tool integrates microcontrollers and sensors to accurately measure both angular and linear velocities. By varying wheel sizes and controlling rotation speeds, students can explore the relationship between speed, size, and motion. Real-time data transmission via smartphones ensures accessibility and efficiency in analyzing wheel dynamics during experiments. The system incorporates a KY-024 Hall effect sensor that detects wheel movements through digital signals generated by magnets. Data is collected in real-time and sent to an IoT platform for further analysis, allowing precise comparisons between experimental and theoretical values. The tool supports three configurations: contacting wheels, concentric wheels, and belt-connected wheels, enabling comprehensive exploration of wheel mechanics. Experimental results demonstrate high accuracy, with angular velocity measurements exceeding 98,00% across configurations. Contacting wheels achieve accuracy levels of 97,68% and 98,34%, concentric wheels maintain 98,34%, and belt-connected wheels exhibit slight variations at 98,34% and 97,65%. This IoT-integrated system offers a reliable, precise, and versatile approach to understanding wheel dynamics, making it a significant asset for enhancing educational physics experiments.